1986
DOI: 10.1002/art.1780290906
|View full text |Cite
|
Sign up to set email alerts
|

Auto antibodies in the cerebrospinal fluid of patients with systemic lupus erythematosus

Abstract: Autoantibodies may play an important role in the pathogenesis of centpal nervous system (CNS) disease in systemic lupus erythematosus (SLE). We obtained cerebrospinal fluid (CSF) and, in some cases, sera from 19 SLE patients with CNS lupus and from 12 SLE patients without CNS lupus. Autoantibodies to saline solable cellular antigens were detected in the CSF of lupus patients and reflected those present in the serum. These antibodies were distinct from the previously described antineuronal antibodies. Analysis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
1
3

Year Published

1988
1988
2009
2009

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 68 publications
(22 citation statements)
references
References 31 publications
0
18
1
3
Order By: Relevance
“…Our previous report (34) demonstrated that anti-cardiolipin antibodies (aCL) purified from SLE sera could bind to brain tissue and damaged astrocytes, an essential component of the blood brain barrier. Because we did not measure the aCL in either serum or CSF, it could not be ascertained if aCL cause leakage of I L 6 &/or IgC from blood to CSE In contrast to the authors who have reported a wide spectrum of brain reactive autoantibodies in the CSF of patients with NP-SLE (14,35,36), we could not detect significant elevation of such antibodies in our limited CSF samples. Again, this inconsistency is possibly due to too small sample size of NP-SLE cases.…”
Section: Csf Changes In Np-sle and Cns Infectionscontrasting
confidence: 80%
“…Our previous report (34) demonstrated that anti-cardiolipin antibodies (aCL) purified from SLE sera could bind to brain tissue and damaged astrocytes, an essential component of the blood brain barrier. Because we did not measure the aCL in either serum or CSF, it could not be ascertained if aCL cause leakage of I L 6 &/or IgC from blood to CSE In contrast to the authors who have reported a wide spectrum of brain reactive autoantibodies in the CSF of patients with NP-SLE (14,35,36), we could not detect significant elevation of such antibodies in our limited CSF samples. Again, this inconsistency is possibly due to too small sample size of NP-SLE cases.…”
Section: Csf Changes In Np-sle and Cns Infectionscontrasting
confidence: 80%
“…23 So, anti-asialo GM1 antibody, anti-ribosomal P protein antibody, and anti-neural cell antibody against neural cells have been detected in both sera and CSF from SLE patients. [23][24][25] More specifically, Kunas and colleagues demonstrated antibodies against dopaminergic cells in serum from a patient with SLE showing PS. According to Kunas and associates, anti-DA antibodies could be specific to neurolupus with parkinsonian symptoms and not a general epiphenomenon of SLE, because they did not detect them in 10 serum or in 2 CSF samples from a control population with serologically and clinically active SLE, 5 of whom had cerebral involvement but no parkinsonism.…”
Section: Discussionmentioning
confidence: 96%
“…The clinical significance of antibodies detected in the CSF of SLE patients is very rarely discussed. Golombek et al [25] demonstrated antiribosomal P protein antibodies in all of four SLE patients with psychosis.…”
Section: Discussionmentioning
confidence: 98%